Examining and extending the influence of presumed influence hypothesis in social media. Issue 3 (4th May 2021) - Cho, Hyunyi; Shen, Lijiang; Peng, Lulu
ABSTRACT: The influence of presumed influence hypothesis (IPI) is a communication theory accounting for the process of persuasive media effects. The present study integrates theoretical perspectives in persuasion and new and traditional media effects research to investigate the assumptions and explanatory mechanisms of IPI in an experiment. View numbers in social media directly predicted presumed exposure by others and indirectly predicted presumed influence on others, consistent with IPI and inconsistent with the bandwagon heuristic. Presumed exposure predicted presumed influence, consistent with IPI. Other predictors of presumed exposure and presumed influence were also found. Self's evaluation of the message (realism) and engagement in the message (identification) predicted presumed exposure by others and presumed influence on others, supporting the expectation that a motivational mechanism of IPI is self-centric social perception. Social media message view numbers did not predict persuasive outcomes directly, but the evaluation of and engagement in the message did. Finally, the data were inconsistent with the assumption of pervasive mass media reach. This study provides theoretical implications for examining persuasive effects of social media messages, while enhancing and expanding IPI. Limitations of the study and directions for future research are discussed.